Development of triple band planar inverted F-antenna (PIFA) for GSM 800 MHz, DCS 1800 MHz and Bluetooth 2400 MHz - Yasin, Mukhtar Ahmed (2015)
A triple band Planar Inverted F-Antenna (PIFA) antenna for GSM900, DCS1800 and Blutooth2400 is presented. The antenna consists of square planar radiating patch with dual L-shaped slots suspended above the FR4 dielectric substrate. A shorting plate is employed between the top patch and the ground plane. The antenna is fed by using coaxial feeding as it is easier to design. The antenna is designed and simulated using CST Microwave Studio. Different parameters such as shorting width, height of antenna, ground plane size and patch slot size that effect PIFA antenna characteristics are also studied. The designed antenna is fabricated, assembled together and tested using network analyzer. The result obtained for the S11 parameter in measurement for the three bands are 0.966 GHz, 1.836 GHz and 2.50 GHz with return loss of -25.84 dB, -32.52 dB and -24.2 dB respectively. Comparison for the measurement and the simulation are carried out in terms of S11 parameter, bandwidth, VSWR, input impedance and radiation pattern.